Plant Characteristics for Green Wall Systems - Irawati, Endah Budi; Basuki (Proceeding International Conference on Science and Engineering, 2020)
This research is a preliminary study of planting ornamental plants with a green wall system. This study aims to provide an overview and information about the selection of types of plants that are suitable and commonly used in making green walls and arranging selected plants in green walls system. Green wall system which is often called vertical garden is a technique to plant ornamental plants, vegetables or other types of plants with a free design that considers various resources that allow plants to grow vertically. The advantages of green walls are efficient use of soil, beautifying the environment, adding location value, cleaning the air, lowering temperature, producing oxygen and providing fresh food that is close to the surrounding environment at home. Not all types of plants can be planted vertically. Easy-to-grow plants, short appearance and slow growth are common characteristics used for green walls. The special characters of the selected plants are determined based on the group of indoor or outdoor plants. Consideration of nutritional, light, water and plant requirements will determine the success of planting and the sustainability of vertical planting.